1989
DOI: 10.1096/fasebj.3.6.2564831
|View full text |Cite
|
Sign up to set email alerts
|

Variable receptor affinity hypothesis

Abstract: Measurements of the contractile response to norepinephrine (NE) of a variety of arteries of three mammalian species that are commonly used in the laboratory provide evidence that tissue sensitivity and affinity of the alpha 1-adrenoceptor for NE covary over a range of several orders of magnitude. The quantitative relationship suggests that variation in affinity can, to a great extent, account for the variation in sensitivity found in a number of circumstances. Furthermore, it is argued that the variation in af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Although the potency of prazosin varied significantly between the species, the values nonetheless fall within the range reported for ai-adrenoceptor block ade [12,13]. Norepinephrine potency also varied among aortae, and this has been shown to correlate with varia tion in receptor affinity and receptor reserve [ 14,21 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although the potency of prazosin varied significantly between the species, the values nonetheless fall within the range reported for ai-adrenoceptor block ade [12,13]. Norepinephrine potency also varied among aortae, and this has been shown to correlate with varia tion in receptor affinity and receptor reserve [ 14,21 ].…”
Section: Discussionsupporting
confidence: 64%
“…It is not apparent why the maximum responses to norepinephrine were not depressed by chlor ethylclonidine. as would be characteristic of an irrevers ible antagonist [11], However, this unusual pattern of antagonism by chlorethylclonidine in vascular tissues has been observed by others [ 19,21 ]. We know that the antag onism of norepinephrine by chlorethylclonidine was, in deed.…”
Section: Resultsmentioning
confidence: 81%
“…could, for example, be related to alterations in agonist affinity for the a,-adrenoceptsr. Investigations in diverse isolated vasculature from several species support such a hypothesis and have shown that variations in the sensitivity of tissue responsiveness to a,-adrenoceptor activation are strongly positively correlated with equivalent alterations in agonist affinity (Bevan et al 1986(Bevan et al , 1988(Bevan et al , 1989Oriowo et al 19887). Moreover, little, if any.…”
Section: Introductionmentioning
confidence: 99%
“…Finally it must be said that the influence of the membraneous environment on the efficacy of hormones and agonists has been neglected. But as long as the molecular mechanisms of receptor activation are unknown, it will remain difficult to explain functional heterogeneity of receptors as a result of environmental effects, as exemplified by the case of vasoconstrictive a,-adrenoceptors which vary in different tissues and in different animal species in ligand affinity and biological activity (Bevan et al, 1989). What applies to p-adrenoceptor activation also applies to desensitization (Hausdorff et al, 1990a; see Fig.…”
Section: )mentioning
confidence: 99%